Design thinking applied to the improvement of citizen competences in university students: popular vote - Hernández-Gil, Cristian; Núñez-López, Jaime Alexis (Universidad Pedagógica y Tecnológica de Colombia, 2020)
The objective of this research was to apply the design thinking technique to improve social thinking skills inside the citizen competences of the students of a Colombian Business Administration program. A qualitative and descriptive study with 48 students of last semesters was carried out, implementing the design thinking methodology in activities inside the classroom with them, In. this case, we worked with two objects: a die and a telephone, and an initiative: awareness-raising towards the conscious exercise of voting. The twelve artifacts created, were subjected to evaluation criteria, especially their capacity so that the problem question could be answered through their operation. The different artefacts built, whose main function is to raise awareness of the exercise of popular vote, were designed based on the principles of solidarity, initiative and inquiry. It was concluded that the application of this methodology promotes the creative development of the students, applied to the participation of the mechanisms to exercise citizen control.